Analysis of Human-Computer Interaction Satisfaction on The Employee Information System at The Department of Education, Bogor Regency (Sakedik) Using The Eucs Method - Aryo Putra Hadiutama; Mahda Yulia Astary; Ire Puspa Wardhani (International Journal Labs, 2025)
The rapid advancement of information technology has encouraged government institutions to adopt electronic-based systems to enhance public service delivery. The Department of Education of Bogor Regency has developed the Personnel Information System (SAKEDIK) to streamline personnel data management. This study aims to evaluate user satisfaction with the SAKEDIK system using the End User Computing Satisfaction (EUCS) method, which assesses five dimensions: content, accuracy, format, ease of use, and timeliness. Data were gathered through questionnaires distributed to 97 respondents and analyzed using the Customer Satisfaction Index (CSI). The results show that overall user satisfaction falls within the